India’s fertilizer policies: implications for food security, environmental sustainability, and climate change - Sapkota, Tek B.; Bijay-Singh (Regional environmental change, 2025)
To ensure food security, the Government of India has implemented various policies since the 1950s to provide enough and affordable fertilizer for farmers. Based on quantitative data, this paper provides a comprehensive and systematic analysis of how these policies influenced the fertilizer consumption and nutrient management and their influence on the socio-economic status of rural producers as well as environmental and climate outcomes. Increases in food grain production have paralleled the consumption of fertilizers. Even though the population of India increased more than three times from 1961 to 2022, per capita availability of rice remained almost the same, and that of wheat increased by 2.4 times. The price of urea has continuously decreased since 1977, but the price of diammonium phosphate fell only after the decontrol of phosphatic and potassium fertilizer in 1992, and the implementation of nutrient-based subsidies in 2010. Fertilizer policies have been linked to reductions in rural poverty and the contribution of agriculture to India’s gross domestic product. However, the overuse of subsidized urea and underuse of phosphatic and potassium fertilizers have resulted in economic and nutrient use inefficiencies, reduced crop yields, and increased environmental risks, including nitrous oxide emissions and nitrate leaching. India’s fertilizer policies must address these environmental challenges while ensuring food security for the growing population. Balanced fertilization should be incentivized through recalibrating subsidies and adopting soil nutrient-based recommendations. Gradual liberalization of urea pricing, alongside measures to ensure the affordability of phosphatic and potassium fertilizers for small and marginal farmers, will be essential to address the food-fertilizers-climatic crisis.